Cognitive Behavioural-Anger Management Training (CB-AMT) Reduce the Student's Aggressive Behavior - Dyah Ayu Kartika Wulan Sari; Fidiana Kurniawati (Jurnal Ilmu Keperawatan Jiwa, 2022)
Students with high levels of anger tend to have destructive coping strategies, express anger by attacking people in physical or verbal forms and experiencing conflicts with others more often. One technique of changing behavior, especially aggression in elementary school students is to develop and implement Cognitive Behavioural-Anger Management Training (CB-AMT) that can be applied in schools. This training is appropriate to be applied to reduce aggressive behavior because of the difficulty of children in managing their anger.The specific purpose of this research is to train each student to be able to use Cognitive Behavioural-Anger Management Training (CB-AMT) techniques to reduce aggressive behavior. The method in this study was a pre-experimental study with a pretest-posttest design. The samples were 70 respondents of school-age children. The sampling used is purposive sampling. Collecting data using observation sheets. The results obtained. Based on the results of the study, it was found that the most respondents had good Aggressive Behavior After Cognitive Behavioural-Anger Management Training (CB-AMT) was 58 respondents (83%). It was concluded that based on the results of research conducted by Cognitive Behavioural-Anger Management Training (CB-AMT) on children at SDN Pakistaji 1 Probolinggo City, it can reduce aggressive behavior in children. Through Cognitive Behavioural-Anger Management Training (CB-AMT) Skills that are carried out and trained together.